Effects of acupuncture in postmenopausal women with prehypertension or stage 1 hypertension: study protocol for a prospective, comparative, interventional cohort study - Bok-Nam Seo; Ji-Eun Park; Young-Eun Kim; Kyung-Won Kang; In-Chan Seol; Sun-Mi Choi (Integrative Medicine Research)
Background: Hypertension is a major cause of cardiovascular disease and associated mortality, and postmenopausal women are at a high risk of hypertension. We aim to investigate the hypotensive effect and safety of acupuncture, focusing on postmenopausal women with prehypertension and stage 1 hypertension. In addition, we aim to investigate whether the effect of acupuncture treatment differed, depending on Sasang Constitution and cold–heat pattern. Methods: This study is designed as an intervention cohort study. Two hundred postmenopausal women aged <65 years with prehypertension or stage 1 hypertension living in Daejeon city in Korea will be recruited, and randomly assigned to either an acupuncture or no-treatment control group. The intervention will consist of four sessions; one session will include acupuncture performed 10 times for 4 weeks. There will be a 20-week observation period after each session, and the total study duration will be 96 weeks. Acupuncture will be applied at the bilateral Fengchi (GB20), Quchi (LI11), Zusanli (ST36), and Sameumgyo (SP6) acupoints. The effect of acupuncture will be evaluated by comparing the change in systolic and diastolic blood pressure between the acupuncture and control groups every 4 weeks until the end of the study. Discussion: To evaluate the success of blood pressure management, long-term observation is required, but no long-term studies have been conducted to evaluate the effect of acupuncture on blood pressure in postmenopausal women. To our knowledge, this study will be the first long-term study to investigate this issue for more than 6–8 weeks. Keywords: Acupuncture, Hypertension, Intervention cohort study, Postmenopausal women, Prehypertension